Randomized controlled clinical study on Yiqi Liangxue Shengji prescription for intervention cardiac function of acute myocardial infarction with ischemia-reperfusion injury. Issue 10 (12th March 2021) - Chen, Cong; Xia, JunYan; Feng, Ruli; Wan, Jie; Zhou, Kun; Lin, Qian; Li, Dong
Abstract: Introduction: The morbidity and mortality of acute myocardial infarction patients still remains high after percutaneous coronary intervention (PCI). Myocardial ischemia-reperfusion (MIR) injury is one of the important reasons. Although the phenomenon of MIR injury can paradoxically reduce the beneficial effects of myocardial reperfusion, there currently remains no effective therapeutic agent for preventing MIR. Previous studies have shown that Yiqi Liangxue Shengji prescription (YLS) is effective in improving clinical symptoms and ameliorating the major adverse cardiovascular events of coronary heart disease patients undergoing PCI. This study aims to evaluate the effectiveness and safety of YLS in patients with acute myocardial infarction (AMI) after PCI. Methods: This study is a randomized, double-blinded, placebo-controlled, single-central clinical trial. A total of 140 participants are randomly allocated to 2 groups: the intervention group and the placebo group. Based on routine medications, the intervention group will be treated with YLS and the placebo group will be treated with YLS placebo. All participants will receive a 8-week treatment and then be followed up for another 12 months. The primary outcome measures are N terminal pro B type natriuretic peptide (NT-proBNP) and left ventricular ejection fraction. Secondary outcomes are plasma levels of microRNA-145, plasma cardiac enzyme, and Troponin I levels in blood samples, changes in ST-segment in ECG, Seattle Angina Questionnaire, the efficacy of angina symptoms, and occurrence of major adverse cardiac events. All the data will be recorded in case report forms and analyzed by SPSS V.17.0. Discussion: The trial will investigate whether the postoperative administration of YLS in patients with AMI after PCI will improve cardiac function. And it explores microRNAs (miRNA)-145 as detection of blood-based biomarkers for AMI by evaluating the relation between miRNAs in plasma and cardiac function. Trial registration: Chinese Clinical Trials Registry identifier ChiCTR2000038816. Registered on October 10, 2020.